Institutional Restructuring of Shibori Sidomaju Elderly Community for Sustainable Business Support - Amir Mahmud; Nurdian Susilowati; Wulan Suci Rachmadani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
The Shibori Sidomaju elderly group is a community that actively produces and sells shibori cloth. As the Shibori Batik business develops, there are many conflicts of interest between members. The management chairman committed fraud by taking over all the assets owned by the community, so the village government took over the management. This community service aims to transfer knowledge regarding institutional strengthening through management reorganization by establishing articles of association, by-laws, and organizational structure. The approach to community service activities used is Participatory Rural Appraisal (PRA) in counseling, mentoring, and training. The target community is the administrators and members of the Batik Shibori Elderly group in Kenteng Village. The activities were carried out from July to August 2023. The results show that Shibori managers understand the importance of institutional legality and the Shibori organizational structure. The output of the activity was the article by law, which was agreed upon and approved by all Shibori members. On this occasion, an organizational structure was also agreed upon that reflects the primary duties of the management, members, and village government. The division of leading tasks and functions can increase the sense of responsibility, commitment, and loyalty. Awareness and understanding of leading tasks and functions are the keys to developing the Shibori business.